IMPLEMENTASI PROGRAM MARKETING PUBLIC RELATIONS MELALUI EVENT ORGANIZER - Melita, Yerah (Istek Widuri Jakarta, 2019)
Every organization or company must have a program or work plan that will be implemented or realized, but in reality not all can implement their own programs. Organizations, companies, or individuals can ask for assistance to the Event Organizer services to be able to succeed the program. To be able to implement an organization or company program especially the Marketing Public Relations program requires hard work, cooperation, and agreement between the two parties, both the organization or company that trusts to carry out the program to the Event Organizer and the party who receives the trust, so that both of them are equally receiving benefits.